Do journal authors plagiarize? Using plagiarism detection software to uncover matching text across disciplines - Sun, Yu-Chih (Journal of English for academic purposes, 2013)
The current study aims to explore the extent of matching text in published journal articles and how the number of authors and their various official languages influence the extent to which matching text appears. Six hundred journal articles in Science, Technology, Engineering, and Mathematics (STEM) and Social Science were randomly selected and screened by both plagiarism detection software (Turnitin) and human raters(s). The results indicate that disciplinary differences do exist in terms of the degree of matching text incidences. Journal articles in STEM tend to contain significantly more consecutive matching text from other sources than Social Science journal articles. However, it is not clear if this is discipline dependent. In addition, authors tended to have more consecutive text copied from their own previously published works than that of others' publications. Furthermore, the greater the number of authors an article has the more consecutive text-matching can be observed in their published works. Additionally, authors located in contexts wherein English is an official language do not differ significantly from those in contexts wherein English is not an official language on their Turnitin scores and the number of 30-word or longer strings of consecutive matching text from self-published articles and self-and-others’ publications combined. •Journal articles in STEM contain significantly more consecutive-text-matching.•Journal authors have more matching text of their own previously published works.•The greater the number of authors an article has, the more text-matching observed.•Official language does not make significant differences on authors' intertextuality.